Comprehensive Characterization of Titania Nanotubes Fabricated on Ti-Nb Alloys: Surface Topography, Structure, Physicomechanical Behavior, and a Cell Culture Assay - Chernozem, Roman V.; Surmeneva, Maria A.; Ignatov, Viktor P.; Peltek, Oleksii O.; Goncharenko, Alexander A.; Muslimov, Albert R.; Timin, Alexander S.; Tyurin, Alexander I.; Ivanov, Yurii F.; Grandini, Carlos R. [UNESP]; Surmenev, Roman A. (Amer Chemical Soc, 2020)
In this study, hybrid composites based on beta-alloy Ti-xNb and oxide nanotubes (NTs) have been successfully prepared. NTs of different sizes were grown on Ti-Nb substrates with different Nb contents (5, 25, and 50 wt %) via electrochemical anodization at 30 and 60 V. Scanning electron microscopy imaging revealed that vertically aligned nanotubular structures form on the surface of Ti-Nb alloy substrates and influence Nb content in alloys based on NT length. X-ray diffraction analysis confirmed the formation of the anodized TiO2 layer and revealed several phases as the Nb content increased, starting with alpha' for low Nb content (5 wt %), the martensite alpha '' for intermediate Nb content (25 wt %), and the beta phase for the highest Nb content (50 wt %). Nanoindentation testing was used to evaluate the changes in mechanical properties of oxide NTs grown on Ti-Nb alloys with different compositions. NT arrays showed wide variations in Young's modulus and hardness depending upon the anodization voltage and the Nb content. The hardness and Young's modulus strongly correlated with NT morphology and structure. The highly dense morphology formed at a lower anodization voltage results in increased elastic modulus and hardness values compared with the surfaces prepared at higher anodization voltages. The nanostructurization of Ti-Nb surface substrates favored improved surface properties for the enhanced adhesion and proliferation of human mesenchymal stem cells (hMSCs). In vitro adhesion, spreading, and proliferation of hMSCs revealed the improved surface properties of the NTs prepared at an anodization voltage of 30 V compared with the NTs prepared at 60 V. Thus it can be concluded that NTs with diameters of similar to 50 nm (at 30 V) are more favorable for cell adhesion and growth compared with NTs with diameters of 80 +/- 20 nm (at 60 V). The surfaces of Ti-25Nb substrates anodized at 30 V promoted enhanced cell growth, as the further increase in Nb content in Ti-Nb substrate (Ti-50Nb) led to reduced cell proliferation. The application of NTs on Ti-Nb substrates leads to significant reductions in mechanical properties compared with those on the Ti-Nb alloy and improves cell adhesion and proliferation, which is vitally important for successful application in regenerative medicine.
Keywords: implant; surface modification; TiNb alloy; anodization; nanotubes